How do Lawyers Examine and Cross‐Examine Children in Scotland?. Issue 6 (26th October 2016) - Andrews, Samantha J.; Lamb, Michael E.
Summary: In the first study to systematically assess lawyers' questioning of children in Scotland, we examined 56 trial transcripts of 5‐ to 17‐year‐old children testifying as alleged victims of sexual abuse, focusing on differences between prosecutors and defense lawyers with respect to the types of questions asked and effects on witnesses' responses. Prosecutors used more invitations, directives, and option‐posing prompts than defense lawyers, who used more suggestive prompts than prosecutors. Children were more unresponsive and less informative when answering defense lawyers than prosecutors. All children contradicted themselves at least once, with defense lawyers eliciting more self‐contradictions than prosecutors. Suggestive questions were most likely to elicit self‐contradictions, with suggestive confrontational and introductory questions eliciting significantly more self‐contradictions than suggestive suppositions. Children also acquiesced more in response to tagged suggestions than untagged suggestions. Overall, lawyers altered their behavior little in response to variations in children's ages. Copyright © 2016 John Wiley & Sons, Ltd.